Pola Spasial Industri Kecil Menengah dan Dampaknya Terhadap Perekonomian Lokal di Kecamatan Tingkir, Kota Salatiga - Riyani, Agustina Dwi; Amrullah, M. Fikri (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2026)
Tingkir District in Salatiga is an area with the highest concentration of Small and Medium Industries (SMIs) that plays a strategic role in strengthening the local economy. The objectives of this study are (1) to analyze the spatial distribution pattern of SMIs, and (2) to determine the impact of their activities on the local community’s economy. The research employs a descriptive quantitative method based on Geographic Information Systems (GIS), using the Average Nearest Neighbor (ANN), Kernel Density, and simple linear regression analysis techniques. The analysis results show a Nearest Neighbor Ratio (NNR) of 0.461 with a p-value of 0.000, indicating that the distribution pattern of SMIs in Tingkir District tends to be clustered and statistically significant. The simple linear regression test produced a coefficient of 0.672 with a significance level of 0.000 (<0.05), suggesting that SMI activities have a positive and significant impact on the local economy, particularly through increased employment absorption, higher household income, and the growth of trade and service sectors. These findings highlight the importance of spatially oriented economic policies to promote sustainable and equitable SMI development in Tingkir District.